2020
DOI: 10.1001/jamanetworkopen.2020.26064
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Severity of Depressive Symptoms Among At-Risk Groups in the UK During the COVID-19 Pandemic

Abstract: Key Points Question Are sociodemographic, psychosocial, and health-related factors associated with risk of poor mental health during the COVID-19 pandemic in the UK? Findings This cohort study using data from a large panel study including 51 417 adults found that the risks of moderate and severe depressive symptom trajectories were significantly higher among people experiencing abuse or low social support, individuals with low socioeconomic position, and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
139
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(161 citation statements)
references
References 37 publications
11
139
3
Order By: Relevance
“…This is the case of age, gender, economic status, and being a student. These findings are congruent with recent studies showing that females, younger people, students, and those with lower economic status may be the most vulnerable to developing psychological problems during the COVID-19 pandemic (e.g., Alonzi et al, 2020 ; Asmundson et al, 2020 ; Fitzpatrick et al, 2020 ; Iob et al, 2020 ; Kajdy et al, 2020 ; Luo et al, 2020 ; Pieh et al, 2020 ; Purtle, 2020 ; Vahedian-Azimi et al, 2020 ; Xiong et al, 2020 ). The results also demonstrated that people with mental disorder diagnosis showed higher levels of all aspects of emotional disturbance than their non-diagnosed counterparts.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is the case of age, gender, economic status, and being a student. These findings are congruent with recent studies showing that females, younger people, students, and those with lower economic status may be the most vulnerable to developing psychological problems during the COVID-19 pandemic (e.g., Alonzi et al, 2020 ; Asmundson et al, 2020 ; Fitzpatrick et al, 2020 ; Iob et al, 2020 ; Kajdy et al, 2020 ; Luo et al, 2020 ; Pieh et al, 2020 ; Purtle, 2020 ; Vahedian-Azimi et al, 2020 ; Xiong et al, 2020 ). The results also demonstrated that people with mental disorder diagnosis showed higher levels of all aspects of emotional disturbance than their non-diagnosed counterparts.…”
Section: Discussionsupporting
confidence: 90%
“…For example, during collective traumas, socially disadvantaged groups generally show worse psychological outcomes than their more advantaged counterparts (e.g., Reid, 2013 ). Several authors noted that mental health consequences due to the COVID-19 pandemic are more pronounced among vulnerable groups, such as females, younger people, people with low income levels, students, and those who are diagnosed with a mental health disorder or have a preexisting physical health condition (e.g., Alonzi et al, 2020 ; Asmundson et al, 2020 ; Fitzpatrick et al, 2020 ; Iob et al, 2020 ; Kajdy et al, 2020 ; Luo et al, 2020 ; Pieh et al, 2020 ; Purtle, 2020 ; Vahedian-Azimi et al, 2020 ; Xiong et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Age was associated with psychological distress, χ 2 (18, N = 12,407) = 762.37, p < 0.001, see Table 3 . Levels of distress were least in the oldest (75+) group, with 33.8% having clinical significance and 8.0% being classified as “severe,” and greatest in the youngest group ( 16 24 ) with 76.6 and 36.2%, respectively. Calculation of odds ratios using the oldest group as the comparison shows that individuals with severe psychological distress are 6.50 times more likely to be in the youngest age group in comparison to the oldest age group.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to pre-pandemic trends, adults with low household income or socioeconomic position reported more anxiety and depression than adults with higher household income or socioeconomic position Iob et al, 2020;Wright, J et al, 2020). Adults who were not in employment were more likely to report increasing levels of loneliness.…”
Section: Introductionmentioning
confidence: 90%
“…On the other hand, there is also evidence of higher mental distress among employed adults, as well as among adults with higher levels of education (Niedzwiedz et al, 2020 ; Pierce et al, 2020 ). The relationship between mental health, wellbeing and ethnicity is unclear with some studies reporting no significant association (Iob et al, 2020 ; Xu & Banks, 2020 ), while others suggest higher levels of mental distress among Asian than White British adults (Niedzwiedz et al, 2020 ; Pierce et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%